Bhambra, G. K., Gebrial, D., & Nişancıoğlu, K. (Eds.). (2018). Decolonising the university. London, England: Pluto Press. (Journal of Applied Learning and Teaching, 2019)
Decolonising the University has a striking book cover, featuring an imagined Cecil Rhodes statue amputated above the ankles with graffiti stating “Decolonising the University” on the pedestal of the statue. The tome features contributions by 20 authors (including the three co-editors). In order to appreciate the battle cry of Decolonising the University, it is useful to clarify the concept of colonialism. In their introductory chapter, Bhambra (a Professor of Postcolonial and Decolonial Studies at the University of Sussex), Gebrial (a PhD student at the London School of Economics) and Nişancıoğlu (a Lecturer in International Relations at SOAS) employ a broad definition of colonialism which is not restricted to ‘settler colonialism’ (for instance, in the Americas), but also includes commercial imperialism, the slave trade, “financialised neo-colonialism” and Orientalism (5). Universities played an important role in various colonial projects by, amongst many other things, developing racist theories and educating future colonial administrators.